2014
DOI: 10.1016/j.clae.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Examination of ocular biomechanics with a new Scheimpflug technology after corneal refractive surgery

Abstract: a b s t r a c tPurpose: To analyze the early results of a new device measuring ocular biomechanics after corneal refractive surgery. Patients and methods: Thirty nine refractive surgery patients were enrolled in the study (age: 32.6 ± 9.9 years). Laser in situ keratomileusis (LASIK) was performed on 52 eyes of 26 patients and photorefractive keratectomy (PRK) was done on 26 eyes of 13 patients. Ten device-specific biomechanical parameters, intraocular pressure (IOP) and pachymetry were measured preoperatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…[13][14][15] The Corvis ST (Oculus Optikgeräte GmbH; Wetzlar, Germany) was later introduced as a noncontact tonometer, which monitors the response of the cornea to an air pressure pulse using an ultra-highspeed Scheimpflug camera, and uses the captured image sequence to produce estimates of IOP and deformation response parameters. 16 Several articles have recently been published on the possible applications of the Corvis ST, particularly evaluating possible biomechanical differences in the cornea after undergoing refractive surgery procedures, [17][18][19][20][21][22] between normal and keratoconic patients, [23][24][25][26] after cross-linking, 27 and in patients with glaucoma. [28][29][30][31] However, it has been demonstrated that IOP and pachymetry have important influences on most corneal biomechanical metrics provided by both the Corvis ST and ORA.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] The Corvis ST (Oculus Optikgeräte GmbH; Wetzlar, Germany) was later introduced as a noncontact tonometer, which monitors the response of the cornea to an air pressure pulse using an ultra-highspeed Scheimpflug camera, and uses the captured image sequence to produce estimates of IOP and deformation response parameters. 16 Several articles have recently been published on the possible applications of the Corvis ST, particularly evaluating possible biomechanical differences in the cornea after undergoing refractive surgery procedures, [17][18][19][20][21][22] between normal and keratoconic patients, [23][24][25][26] after cross-linking, 27 and in patients with glaucoma. [28][29][30][31] However, it has been demonstrated that IOP and pachymetry have important influences on most corneal biomechanical metrics provided by both the Corvis ST and ORA.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper (), a profiled script written in Python and ImageJ v1.46 was applied. In terms of changes in deformation parameters over time, Hassan et al presented an interesting analysis in paper . They performed laser in situ keratomileusis (LASIK) on 52 eyes of 26 patients and photorefractive keratectomy on 26 eyes of 13 patients.…”
Section: Critical Summarymentioning
confidence: 99%
“…carried out a comparison of the corneal biomechanical parameters variation between PRK and LASIK using Corvis; they observed that most of these biomechanical parameters remained unchanged after one month of LASIK and PRK compared to the preoperative data [23]. …”
Section: Introductionmentioning
confidence: 99%